Quranic Tadabbur on Gus Baha’s Sermons in the Santri Gayeng YouTube Channel: Critical Discourse Analysis - Ahmad , Khamim Jazuli; Quthrunada , Safiatuddina; Noorhidayati , Salamah; Siti Marpuah (Journal of Quranic Sciences and Research, 2025)
Quranic tadabbur is the practice of deeply reflecting on the meanings and messages of the Qur’an in order to understand and apply its guidance in daily life, as encouraged by Allah in Surah Muhammad (47:24), which calls believers to contemplate the verses of the Qur’an. In the context of Indonesia, the tadabbur became the content of sermons. Therefore, this study aims to analyze the construction of tolerance discourse in the sermons of Gus Baha delivered through the Santri Gayeng YouTube channel, employing Norman Fairclough’s model of Critical Discourse Analysis (CDA). The research is grounded in the urgency of promoting inclusive religious narratives within Indonesia’s pluralistic society and the growing influence of digital Islamic preaching. A qualitative approach was employed, utilizing transcription, participatory observation, and content analysis of sermon videos that focused on the theme of tolerance. The findings reveal that Gus Baha constructs tolerance discourse through narrative linguistic strategies, the use of local language, and a grounded and reflective rhetorical approach. His sermons transcend conveying theological doctrine by fostering a collective awareness of the importance of peaceful coexistence in diversity. The finding of this research lies in its exposition of how Gus Baha’s digital sermons serve not only as a medium of religious transmission but also as a discursive arena that shapes moderate, peaceful, and context-sensitive Islamic perspectives. The implications indicate the substantial potential of digital da’wah rooted in local wisdom to strengthen religious tolerance and moderation amid the increasing complexity of the digital public sphere